Impact of globalization on growth, poverty and income inequality: a study of Ethiopia and India - Ramakrishna, G.; Sukar, Abdul Hamid; Sivarama Krishnan, V. (2003)
This paper is an effort to study the impact of Globalization on growth, poverty and inequality in Ethiopia and India, which have have attempted open policy measures since 1990s. We have provided a summary analysis of their progress over a long period. The data indicates that both countries have benefited significantly and have shown improved economic performance due to globalization policies. The empirical model used by the study indicates that globalization has resulted in increasing growth in both the countries. Available evidence suggests that the general poverty had declined and human development improved in both the countries. However, the evidence on spatial inequalities is not adequate in India, and for Ethiopia, the non-availability of data poses a big problem in providing it. - Reproduced.
Keywords: Income distribution - Ethiopia; Income distribution - India; Economic growth - Ethiopia; Economic growth - India; Poverty - Ethiopia; Poverty - India; Globalization - Ethiopia; Globalization - India; Globalization